Exploring Clinician Barriers and Enablers in Referring Patients to a Virtual Hospital for Acute Care - Emily Kirkpatrick (Asia Pacific Journal of Health Management)
Background: Virtual hospitals offer a promising solution to alleviate pressures on traditional healthcare systems by providing acute care in patients' homes. Despite the implementation of a virtual hospital model in South Australia, referral rates remain below expectations.